ASSESSMENT OF THE ACUTE DERMAL TOXICITY POTENTIAL OF NATURAL VETERINARY MEDICINE MINYAK RAJAS IN WISTAR RATS - Merdana, I Made; Azizati, ST Kholifah Nor; Arjana, Anak Agung Gde; Adi, Anak Agung Ayu Mirah; Sudira, I Wayan (Buletin Veteriner Udayana; Vol. 12 No. 2 August 2020DO - 10.24843/bulvet.2020.v12.i02.p16, 2020)
Toxicity testing of a new product or drug that will circulate in the market is commonly done to determine its efficacy and safety. This study aims to assess the potential toxicity of the dermal acute natural veterinary medicine of Minyak Rajas on female Wistar rats. The test method used refers to the Organization for Economic Co-operation and Development protocol test number 402 of 2017. The test results obtained primary irritation index of zero, and the median acute dermal lethal dose >2000 mg/kg. It can be concluded that Minyak Rajas does not cause acute dermal toxicity topically and is safe for usage.